2011
DOI: 10.1039/c0sc00578a
|View full text |Cite
|
Sign up to set email alerts
|

Passivating surface states on water splitting hematite photoanodes with alumina overlayers

Abstract: Hematite is a promising material for inexpensive solar energy conversion via water splitting but has been limited by the large overpotential (0.5-0.6 V) that must be applied to afford high water oxidation photocurrent. This has conventionally been addressed by coating it with a catalyst to increase the kinetics of the oxygen evolution reaction. However, surface recombination at trapping states is also thought to be an important factor for the overpotential, and herein we investigate a strategy to passivate tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

60
835
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 789 publications
(899 citation statements)
references
References 36 publications
60
835
2
2
Order By: Relevance
“…Similar looking impedance spectra have recently been reported for hematite electrodes, and a variety of equivalent circuits put forth interpret these spectra. 11,45 In these analyses, the low frequency semicircle is generally attributed to the series arrangement of the depletion capacitance of the semiconductor SC C and the Helmholtz capacitance at the electrode surface, and the role of surface states has largely been ignored.…”
Section: Resultsmentioning
confidence: 99%
“…Similar looking impedance spectra have recently been reported for hematite electrodes, and a variety of equivalent circuits put forth interpret these spectra. 11,45 In these analyses, the low frequency semicircle is generally attributed to the series arrangement of the depletion capacitance of the semiconductor SC C and the Helmholtz capacitance at the electrode surface, and the role of surface states has largely been ignored.…”
Section: Resultsmentioning
confidence: 99%
“…For example, reaction of silicon with HF can suppress surface recombination and improve the performance of photovoltaic devices [138]. For Fe 2 O 3 photoanodes it has been shown that application of Al 2 O 3 [151] or SnO 2 [152] overlayers also improves the performance. For BiVO 4 photoanodes, both application of an SnO 2 underlayer [153], and incorporation of W dopants boost the electrical power output, which is attributed to reduction of surface recombination Fig.…”
Section: Electron-hole Recombinationmentioning
confidence: 99%
“…Illumination on hematite induces the accumulation of photogenerated charges at the interfaces, in particular, hole congregation at the semiconductorelectrolyte junction due to the low mobilities for the charge carriers and the slow kinetics of the oxygen generation reaction. 21,22 Small transient response with our bare hematite may be due to dense nature of film with low surface area. For the Co-Pi/hematite sample (Figure 3), an anodic current spike is also observed during this charge accumulation phase, which decreases rapidly with time and forward potential sweep because the accumulated holes disorder the charge dissemination in the space charge layer.…”
mentioning
confidence: 93%
“…The current linearly increases with increasing potential up to ~1.35 V and begins to decline before sharply increasing at 1.65 V vs. RHE, consistent with the behavior reported for hematite photoanodes. 21 On the Co-Pi/hematite, the photocurrent onset occurs at ~ 0.8 V vs. RHE. In addition, the current increases along with a positive sweep and begins to decline once a higher potential regime is reached (Figure 3a).…”
mentioning
confidence: 99%